A Rare Case of Severe Hypercalcemia Secondary to Atypical Parathyroid Cystic Adenoma with Negative Sestamibi Scan - Monsour, Elio P (Cureus, 2020)
The two types of parathyroid cysts are functional and non-functional cysts. Cystic parathyroid lesions are a rare cause of hypercalcemia and often pose a diagnostic challenge due to the reduced detection on preoperative imaging studies. We, herein, present a rare case of an elderly female presenting to the emergency department with altered mental status associated with hypercalcemic crisis and a negative sestamibi scan. Following surgical resection, pathology revealed the diagnosis of cystic parathyroid adenoma and normalization of serum calcium levels.